The Singapore Convention on Mediation: A Commentary - ALEXANDER, Nadja (Institutional Knowledge at Singapore Management University, 2019)
The Singapore Convention on Mediation is just beginning its life as an international legal instrument. How is it likely to fare? In this first comprehensive, article-by-article commentary, the authors provide a robust report on the features of the Convention and their implications, with analysis of potential controversies and authoritative clarifications of particular provisions.The book’s meticulous examination considers these issues and topics:international mediated settlement agreements as a new type of legal instrument in international lawtypes of settlement agreements that fall within the scope of the Conventionhow the Convention’s enforcement mechanism worksthe meaning of ‘international’ and the absence of a seat of mediationthe Convention’s approach to recognition and enforcement of international mediated settlement agreementsthe grounds for refusal to grant relief under the Conventionmediator misconduct as a ground for refusal to grant reliefthe impact of the Convention on private international lawthe relationship of the Singapore Convention to other international instruments such as the UN Model Law on International Commercial Mediation and the New York Convention on Arbitrationpossibilities for Contracting States to declare reservationsThis book takes a giant step towards relieving the inherent uncertainty associated with how this newly constituted instrument may operate, and how States may become ‘Convention ready’. It is sure to become an essential reference for international lawyers, mediators and government officials as the Convention proves itself in the coming years.